A Chemiluminescence Enzyme Immunoassay Based on Biotinylated Nanobody and Streptavidin Amplification for Diazinon Sensitive Quantification - Pengyan Guo; Kaiyin Huang; Zijian Chen; Zhenlin Xu; Aifen Ou; Qingchun Yin; Hong Wang; Xing Shen; Kai Zhou (Biosensors, 2023)
The advantages of genetic modification and preferable physicochemical qualities make nanobody (Nb) easy to develop a sensitive and stable immunosensor platform. Herein, an indirect competitive chemiluminescence enzyme immunoassay (ic-CLEIA) based on biotinylated Nb was established for the quantification of diazinon (DAZ). The anti-DAZ Nb, named Nb-EQ1, with good sensitivity and specificity, was obtained from an immunized library via a phage display technique, where the molecular docking results indicated that the hydrogen bond and hydrophobic interactions between DAZ and complementarity-determining region 3 and framework region 2 in Nb-EQ1 played a critical role in the Nb-DAZ affinity processes. Subsequently, the Nb-EQ1 was further biotinylated to generate a bi-functional Nb-biotin, and then an ic-CLEIA was developed for DAZ determination via signal amplification of the biotin–streptavidin platform. The results showed that the proposed method based on Nb-biotin had a high specificity and sensitivity to DAZ, with a relative broader linear range of 0.12–25.96 ng/mL. After being 2-folds dilution of the vegetable samples matrix, the average recoveries were 85.7–113.9% with a coefficient of variation of 4.2–19.2%. Moreover, the results for the analysis of real samples by the developed ic-CLEIA correlated well with that obtained by reference method GC-MS (R2 ≥ 0.97). In summary, the ic-CLEIA based on biotinylated Nb-EQ1 and streptavidin recognition demonstrated itself to be a convenient tool for the quantification of DAZ in vegetables.